PELATIHAN PEMBUATAN VIDEO / FILM PENDEK UNTUK SEKOLAH MENENGAH ATAS MUHAMMADIYAH DI PONTIANAK - Octariadi, Barry Ceasar; Sucipto, Sucipto; Putri, Alya Amanda (Jurnal Abdimas Bina Bangsa, 2025)
Film is a tool to convey various messages to the general public through the medium of stories, and can also be interpreted as a medium of artistic expression for artists and filmmakers to express their story ideas. The making of this short film began before production by having an idea of ​​what to show from the story side and to support the appearance of the film to be more interesting and attract the attention of the audience. In addition, the storyline is played backwards, telling the background of the incident. Held in Pontianak, October 3, 2024, it was divided into 2 (two) Socialization and Workshop sessions and was attended by 40 high school and vocational high school students from Muhammadiyah Pontianak. A short film competition was held with the theme "why should I go to college"